FACTORS SHAPING THE LOYALTY OF GENERATION Z WEST JAKARTA IN USING GOPAY - Vivian , Vivian; Utama, Louis (Graduate Program of Universitas Tarumanagara, 2024)
This research aims to examine user experience, perceived ease of use, perceived usefulness and user satisfaction with the loyalty of the West Jakarta generation Z in using GoPay. Then user satisfaction as a mediator of user experience on loyalty. The sample used in this research was 177 generation Z from West Jakarta who used the GoPay digital wallet service. Data was obtained through a questionnaire on line using the help of a Google form then distributed via social media using non-probability sampling techniques and convenience sampling methods. Then the data obtained was processed using PLS-SEM assisted by SmartPLS 3.0 software. The results obtained in this research indicate that a) user experience has an influence on satisfaction. b) user experience has no influence on loyalty. c) perceived ease of use has no influence on loyalty. d) perceived usefulness have an influence on loyalty. e) user satisfaction has an influence on loyalty f) user experience has an influence on loyalty through the mediation of user satisfaction. This research was created with the aim of contributing to PT Dompet Anak Bangsa to carry out development by paying attention to aspects that can maintain the loyalty of GoPay users. Such as providing attractive applications to support transaction activities, providing a good experience in transactions, paying attention to the ease of using digital wallets, features that are easy to use and do not require excessive effort in using the GoPay application to carry out transactions to maintain user loyalty.